1984
DOI: 10.1021/jm00376a024
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive activities of phenyl aminoethyl sulfides, a class of synthetic substrates for dopamine .beta.-hydroxylase

Abstract: Four sulfur-containing analogues of phenylpropylamine were synthesized and evaluated as substrates for dopamine beta-hydroxylase (DBH) and monoamine oxidase (MAO). All four phenyl aminoethyl sulfides were shown to be good substrates for DBH whereas only the two analogues not possessing a methyl group alpha to the terminal amino group were substrates for MAO. All four analogues were tested for acute antihypertensive activity in an animal model for hypertension, the spontaneously hypertensive rat (SHR). Two of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…administration. Padgette et al (1984) found a hypotensive effect of 4-S-CAP which reached a maximum of 25% at 1 h postinjection with a gradual return of the blood pressure to hypertensive levels after 3h.…”
Section: In Vivo Antimelanoma Effectmentioning
confidence: 85%
“…administration. Padgette et al (1984) found a hypotensive effect of 4-S-CAP which reached a maximum of 25% at 1 h postinjection with a gradual return of the blood pressure to hypertensive levels after 3h.…”
Section: In Vivo Antimelanoma Effectmentioning
confidence: 85%
“…The pmethoxyphenethylamine hydrochloride and phenethylamine were obtained from Sigma, and the phenethylamine was crystallized as the hydrochloride salt by standard procedures . The /)-hydroxyphenyl-2-aminoethyl sulfide was prepared in our laboratory as described previously (Padgette et al ., 1984) . Percoll, penicillin/streptomycin/neomycin mixture (PSN; 5,000 U/ml of penicillin O, 5 mg/ml of streptomycin, 10 mg/ml of neomycin in 0.9% saline), gentamycin, glutamine, theophylline, unlabeled dopamine hydrochloride, unlabeled tyramine, and trypan blue were from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Chemicals L-dopa, L-ascorbic acid, Lcysteine, NP40, mushroom tyrosinase (4900 units/mg), and plasma MA0 (1000 units/g), were all obtained from Sigma Chemical Co. (St. Louis, MO). 4-S-CAP and a-Me-4-S-CAP were prepared by the methods of Padgette et al (1984). 4-S-HomoCAP was prepared by adapting our previous methods (Mura et al, 1987;Ito et al, 1981) used for the preparation of 4-S-CAP.…”
Section: Methodsmentioning
confidence: 99%
“…The oxidation of tyrosinase-specific substrates to produce cytotoxicity is the basis for the development of a chemotherapeutic agent against melanoma (Wick, 1980). However, in developing hypotensive agents, Padgette et al (1984) prepared 4-S-CAP and found it to be a good substrate for plasma MA0 as well. Kawase et al (1982) reported that various 3-substituted propylamines exerted cytotoxicity through the production of aldehydes by enzymic oxidative deamination using plasma amine oxidase.…”
Section: Introductionmentioning
confidence: 99%